A Natural Ethics of Gratitude - William M. OʼMeara (Athens Journal of Humanities & Arts, 2019)
Cicero has affirmed that gratitude "is not only the greatest of virtues but the parent of them all" (Pro Plancio, #80). This paper will argue against Kantʼs defense of the second formulation of the categorical imperative by attempting to show that no rational argument can prove the basic principle of morality but that it is a deeply felt and profound choice of the central value of the dignity of person both in oneʼs own life and the lives of all others. Then, following Cicero, this paper will explore how we can find a deeply felt and profound choice of gratitude at the center of the virtues of faith, hope and love. The paper is not arguing that everyone must find gratitude at the heart of faith, hope, and love, but that it is possible to do so. Next, this paper will examine how gratitude can be found at the center of the virtues of practical reason, courage, temperance, and justice. The paper is not arguing that everyone must find gratitude at the heart of practical reason, courage, temperance, and justice, but that it is possible to do so. Finally, this paper will reflect with Augustine and Aquinas on the centrality of the virtue of love in all other virtues and on how love leads to gratitude.